(untitled) (Czech Journal of Multidisciplinary Innovations, 2025)
Information technology applications represent a fundamental challenge to the future of the tourist guidance profession. From this standpoint, the study aims to identify the most important applications of information technology in digital tourist guidance, and to explore the opinions of tourist guides about the skills, applications and challenges of digital tourist guidance. The study relied on the descriptive analytical approach and the survey approach in applying the electronic questionnaire to a random sample of tourist guides in the city of Karbala, the size of which was (59 individuals). The study concluded that there is a statistically significant relationship between tourist guidance performance skills and digital tourist guidance applications, and the presence of a statistically significant impact of digital tourist guidance applications on the challenges of tourist guidance, and the presence of statistically significant differences between the opinions of tourist guides about digital tourist guidance applications. The study recommended developing the performance of tourist guides to keep pace with modern technological developments in the field of tourist guidance by providing training courses and financial allocations.